Mixed Alkali Effect on Viscosity of Sodium Potassium Borate Glasses - Saad B. H. Farid (Engineering and Technology Journal, 2008)
The effect of the alkali oxide content on viscosity has been studiedfor sodium-potassium borate glasses. The deviation of viscosity values fromadditivity has been modeled to investigate the effect of partial substitutionof one alkali oxide for another. Published data on isokom temperatures andactivation energies for sodium-potassium borate glass compositions hasbeen utilized along with L2-regression optimization technique for analysis.It is found that both linear and nonlinear relations determine theviscosity coefficients associated with chemical components of the glassesunder study. This model allows the calculation of viscosity for a giventemperature and accordingly, the fusion temperature of these glasses.Furthermore, the established model relations show first and second ordermixed alkali effect on viscosity.